MCDONALD'S POLICY AND GLOBAL INTEGRATION PROCESS DURING THE COVID-19 PANDEMIC - Boboqulov Oybek Norbutayevich (Bright Mind Publishing, 2025)
This project examines the impact of McDonald’s policies and global integration processes during the COVID-19 pandemic. The pandemic has disrupted global supply chains and changed consumer behavior, which has had a significant impact on the restaurant business during its time. The study analyzes the strategies McDonald’s has used to adapt to these changes, including digital transformation, menu simplification, increased safety measures, and adaptation to local conditions. From a global integration perspective, the project examines the differences in McDonald’s policies and operational practices in different countries. With the onset of the pandemic, McDonald’s has been trying to strike a balance between coordinating global policies and responding to the requirements of local authorities. The project covers issues such as adapting corporate policies to local conditions, relationships with franchisees in different regions, and ensuring the sustainability of supply chains. The results of this project demonstrate McDonald’s resilience and innovation during the pandemic. At the same time, they highlight the benefits and limitations of global integration, especially the trade-off between coordinating corporate policies and responding to local needs during a crisis. The findings suggest that McDonald’s and other global corporations can be key in developing strategies to prepare for future crises, ensure the stability of their supply chains, and adapt to local conditions.
Keywords: COVID-19, McDonald’s, global integration, policy, digital transformation, supply chain, resilience, restaurant business.